Cloud Computing and High Performance Computing (HPC) Advances for Next Generation Internet (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
Cloud computing and high-performance computing have emerged as transformative paradigms reshaping the information and communication technology landscape. This reprint explores cutting-edge advancements and breakthrough research in the field to address critical challenges. Key topics include high-availability solutions in container platforms; AI-driven predictions for cloud pricing; dynamic redundancy models for balancing cost and reliability in clouds; IoT and edge computing for smarter building solutions; transparent performance debugging for microservices; game-theoretic pricing mechanisms for fair and efficient cloud resource allocation; innovative tools for GPU virtualization and optimization in HPC systems; real-time workload optimization for crowdsourced platforms; advanced genomic sequence alignment techniques using HPC; and automated resiliency enhancements for distributed applications. By focusing on practical applications and innovative methodologies, the collection offers valuable insights for shaping the next-generation Internet.